GAME-MODE ACTIVATED: BUILDING COMMUNITIES OF PRACTICE THROUGH DIGITAL ESCAPE ROOMS AS ESP TEACHING AND LEARNING TOOLS - MUDURE-IACOB, Ioana (Studia Universitatis Babeș-Bolyai Philologia, 2024)
Game-Mode Activated: Building Communities of Practice through Digital Escape Rooms as ESP Teaching and Learning Tools. The paper aims to explore the creative potential and practical use of digital escape rooms as innovative and multimodal tools for the building of communities of practice within English for Specific Purposes education. Designed and customised for ESP courses, digital educational escape rooms can present a valuable opportunity to engage learners in an immersive, interactive, and collaborative experience meant to enhance the development of language and creative thinking skills. The study explores how the incorporation of escape rooms as ESP formative assessment may facilitate learning by allowing students to develop communities of practice based on experiential learning, by shedding light on the challenges and opportunities raised by this educational approach. It also analyses how the design and use of escape rooms as an effort to employ digital pedagogical competence can boost motivation among language learners while also creating a socio-emotional learning environment. In order to investigate the pedagogical value of escape rooms, this paper outlines the design process, the targeted learning paths, the multimodal storyline, as well as the ESP-specific content organised as puzzles, tasks, and activities embedded in the escape room. A digital escape room meant to teach and assess language, digital, and communication competences for undergraduates majoring in the Pedagogy of Preschool and Primary Education is exemplified, the study sharing results obtained from a questionnaire administered to undergraduate students based on their experience of completing digital escape room sessions. Digital escape rooms can provide impactful learning environments for a social-emotional framework of teaching ESP, while also allowing participants to bond into communities in practice where they interact by putting to test their 21st century skills. REZUMAT. Modul de joc activat: construirea comunităților de practică prin jocuri digitale de tip „escape rooms” ca instrumente de învățare și predare a limbajelor specializate. Articolul își propune să exploreze potențialul creativ și utilizarea practică a activităților escape rooms ca instrumente inovatoare și multimodale pentru construirea comunităților de practică în cadrul predării și învățării limbii engleze specializate. Proiectate și personalizate pentru cursurile ESP, escape rooms educaționale pot oferi o oportunitate valoroasă de implicare a cursanților într-o experiență interactivă și colaborativă menită să îmbunătățească dezvoltarea abilităților lingvistice și de gândire creativă. Studiul explorează modul în care integrarea camerelor de evadare ca evaluare formativă ESP poate facilita învățarea, permițând studenților să dezvolte comunități de practică bazate pe învățarea experiențială, arătând și provocările și oportunitățile ridicate de această abordare educațională. De asemenea, analizează modul în care proiectarea și utilizarea escape rooms pe baza competențelor pedagogice digitale poate stimula motivația între cursanții de limbi străine, creând totodată un mediu de învățare socio-emoțional. Pentru a investiga valoarea pedagogică a escape room-urilor, lucrarea prezintă procesul de proiectare a activităților de învățare, multimodalitatea și conținutul specific ESP organizat sub formă de puzzle-uri și sarcini de lucru. Studiul exemplifică structura și impactul unui escape room pentru studenții de licență la Pedagogia Învățământului Primar și Preșcolar, împărtășind rezultate obținute dintr-un chestionar administrat studenților bazat pe experiența lor de completare a sesiunilor de escape room. Acest tip de învățare prin escape room poate oferi medii de învățare de impact, configurând învățarea socio-emoțională pentru cursurile de engleză pentru limbaje specializate, permițând totodată participanților să interacționeze în cadrul comunităților de practică. Cuvinte-cheie: multimodalitate, escape rooms, învățare experiențială, gamificarea evaluarii formative Article history: Received 14 March 2024; Revised 24 June 2024; Accepted 15 October 2024; Available online 10 December 2024; Available print 30 December 2024.